Elektronsko literarno besedilo, ki se briše in izginja - Strehovec, Janez (Primerjalna književnost, 2015)
The new media, the internet of things, ubiquitous computing, social networking, and post-internet art address not only images and the visual, but are also directed towards the textual, discovering its new possibilities. In the paradigm of the new media and the digital, this article also applies a new approach to the issue of vanishing and erased text, which was already introduced by modern poetry. This issue is connected with Walter Benjamin%s theory of the second technology, the implications of which are also discovered in the field of playful and rich experience.
Keywords: Benjamin, Walter; elektronska književnost; elektronsko literarno besedilo; izkustvo verbalnega; kulturne inovacije; nove tehnologije; novi mediji